EVALUATION AND INTERVENTION IN DOWN SYNDROME (Fiep Bulletin - online, 2015)
The aim of this study was to verify the motor and biopshychosocial profile from 09 schoolars with Down syndrome, aged 04 to 14 years and to analyze the influence of a specific pshychomotor intervention program in one of those children. For motor evaluation, Motor Development Scale was used - EDM (ROSA NETO, 2002) that evaluates the areas: fine motricity, global motricity, balance, corporal outline, space organization, temporary organization / language and laterality. The bipshychosocial evaluation used a questionnaire elaborated by Rosa Neto and Almeida (2004). In intervention process were used activities for each area of motor development, according to specific program, being interventions followed up daily (SÁNCHES, 2003), accomplished with a 7 year-old child, for 4 months (30 sessions). For data analysis was used the software EPI INFO 2000 (CDC, 2004), the motor profile graphs (ROSA NETO, 2002) and an anecdotary. About sample motor profiles (N=9), 100% presented a classification level "very inferior", especially in global motricidade and language areas. In the laterality, most (78%) presented crusade or indefinite, what could suggest deviations. About the intervention ( case study), quantitative and qualitative earnings were observed in all of motor areas. By EDM, the child presented 10 months of motor earnings. The parents and techers' depositions confirm the positive result.
Keywords: Motor evaluation. Intervention. Down Syndrome.